Penerapan Psak 57 Terhadap Perusahaan Rekayasa, Pengadaan, dan Konstruksi PT Wijaya Karya Tbk - Salsabila, Nadia; Hayuningtyas, Roro; Wulaningsih, Ririn Widyastuti; Mais, Rimi Gusliana; Safitri, Raisa Arifahani (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This investigate points to analyze the Statement of Financial Accounting Standards 57 concerning Provisions, Contingent Liabilities and Contingent Assets on toll road construction projects conducted by PT Wijaya Karya Tbk (WIKA) in 2023, one of leading construction companies in Indonesia. This research utilizes descriptive qualitative by analyzing financial reports. The data collected based on company annual reports and other relevant sources. The research results in the implementation of Statement of Financial Accounting Standards 57 by PT Wijaya Karya Tbk which has been running well, especially in recognizing provisions related to obligations arising from toll road construction projects. However, there are challenges in disclosing contingent liabilities that require further transparency. This research provides important insights regarding company compliance with applicable accounting standards as well as identifying challenges and opportunities in managing provisions, contingent liabilities, and asset liabilities. The findings of this research are expected to be used as a contribution to the better and more transparent development of accounting practices in Indonesia’s industry of construction